Improving quality and appearance of Sungai Belat using activated carbon in riverbank filtration method : a laboratory testing - Nur Sakinah , Ramlan (2014)
Water is indeed important in our daily lives. Demand for good quality of water happened to increase due to an increase in population, rapid urbanization, industrial expansion and climate change. One of the main sources of water comes from surface water such as rivers, lakes and ponds. River water quality is an important parameter that must be preserved and monitored. In order to improve the quality of the water, water treatment has to be conducted. Water from rivers is commonly treated conventionally using chemicals for removal of suspended solids and other contaminants. One of the alternative ways to improve the water quality from rivers is by using Riverbank Filtration (RBF) method. It is used as an alternative for an efficient and economical drinking-water treatment technology. The efficiency of RBF system depends heavily on the type and properties of soil resides in the riverbank. Thus, the efficiency might vary and some modification may be required in achieving reasonable treatment ability. In this study, soil from Sungai Belat riverbank was considered and the effectiveness in improvingthe quality and appearance of water sample was investigated. In addition, AC mixture was also used to modify the soil. Several tests, namely adsorption test and filtration test was conducted in the laboratory to determine the effectiveness of both material as RBF media. In this study, four parameters are considered which are turbidity, colour, total suspended solid (TSS) and total dissolved solid (TDS) and then be compared with Interim National Water Quality Standard (INWQS). Laboratory investigation indicated that, the overall results shows that the type of soil is poorly graded sand with clay (silty clay) (SP-SC). The initial parameter of the river water falls under class II in INWQS where further water treatment is needed. The final results for the water quality parameters by natural soil are: Turbidity; 2.75 NTU, Colour; 38 PtCo, TSS; 0 mg/L and TDS; 117.26 mg/L. While the final results for the water quality parameters by modified soil with AC are Turbidity; 7.06 NTU, Colour; 73.8 PtCo, TSS; 17 mg!L and TDS; 111.2 mg/L. Although the value for turbidity and colour is slightly higher than the maximum value in INWQS, all other parameters are in the range of class I where no further treatment is needed. The quality and appearance of the river water was improved after filtering and thus the natural soil and modified soil with AC can be used as filtration media in the construction of RBF system in treating Sungai Belat.